Career Strategies of Millennial Generation Female Assistant Coaches - Erin Morris; Skye Arthur-Banning; Jacqueline McDowell (University of Kansas Libraries, 2014)
The rate of collegiate female coaches is at an all-time low; but there has been limited research on what might help female coaches succeed. The millennial generation, who grew up with increased athletic opportunities provided by Title IX, is entering the profession, and they may have different views of coaching and athletics than previous generations. The purpose of this study was to investigate what factors influenced millennial generation, female assistant coaches' aspirations to become head coaches and what strategies they believed would help them successfully navigate their careers. The authors interviewed 10 millennial generation, Division I female assistant coaches and found leadership as athletes, appropriate education, and coaching networks, particularly with female coaches, were common strategies for feeling confident in their careers. These findings may help athletic departments create tools, such as women's only coaching clinics, to help encourage women to become and remain coaches and provide them with the required support.